Synergistic Effect of Chitosan and Selenium Nanoparticles on Biodegradation and Antibacterial Properties of Collagenous Scaffolds Designed for Infected Burn Wounds - Dorazilová, Jana (Nanomaterials (Basel), 2020)
A highly porous scaffold is a desirable outcome in the field of tissue engineering. The porous structure mediates water-retaining properties that ensure good nutrient transportation as well as creates a suitable environment for cells. In this study, porous antibacterial collagenous scaffolds containing chitosan and selenium nanoparticles (SeNPs) as antibacterial agents were studied. The addition of antibacterial agents increased the application potential of the material for infected and chronic wounds. The morphology, swelling, biodegradation, and antibacterial activity of collagen-based scaffolds were characterized systematically to investigate the overall impact of the antibacterial additives. The additives visibly influenced the morphology, water-retaining properties as well as the stability of the materials in the presence of collagenase enzymes. Even at concentrations as low as 5 ppm of SeNPs, modified polymeric scaffolds showed considerable inhibition activity towards Gram-positive bacterial strains such as Staphylococcus aureus and methicillin-resistant Staphylococcus aureus and Staphylococcus epidermidis in a dose-dependent manner.